Permanent Pacemaker for Sick Sinus Syndrome with Absent Right Superior Vena Cava A Case Report. - Chanda, PK; Ahmed, N; Biswas, S; Mehedi, MM; DasGupta, S; Rahman, MA; Ahmed, F (Cardiovascular Journal, 2011)
A 42 year old patient, admitted into our hospital for permanent implantation. Implantation of a permanent pacemaker was attempted by the transvenous approach via venous puncture of cephalic vein & subclavian vein on both sides but guide wire failed to pass. Coronary angiogram with cardiac catheterization was done & revealed absence of right superior vena cava and presence of persistant left superior vena cava. Under endotracheal general anesthesia (GA) with limited left thoracotomy epicardial pacemaker was implanted. Key Words: Permanent pacemaker; superior vena cava; persistent left superior vena cava DOI: http://dx.doi.org/10.3329/cardio.v3i2.9195 Cardiovasc. J. 2011; 3(2): 230-232